TRANSPARANSI, AKUNTABILITAS PELAYANAN BADAN PENYELENGGARA JAMINAN SOSIAL ( BPJS ) KESEHATAN DI SURAKARTA - Suhita, Damayanti (Transformasi, 2014)
BPJS Kesehatan is a government-owned company that in charge in health care benefits for thepeople of Indonesia under Law no.24 th 2011. Community to address concerns over theimplementation of this program in BPJS Kesehatan transparency, the entire process, institutions,and information needs to be accessed by interested parties, and provided sufficient information tobe understood and monitored. Accountability ready to account for public funds and to answerquestions either directly or via the web wherever officially provided by BPJS KesehatanKey words: Transparency, Accountability, Services, Social Security Agency, (BPJS) health